INCREASING AN ACCOUNTABILITY OF VILLAGE FINANCIAL MANAGAMENT WITH APPARATUS COMPETENCE AND GOVERNMENT'S INTERNAL CONTROL SYSTEM - Rosari, Renya; Aprilia Manabulu, Herry (Universitas Airlangga, 2020)
The purpose this studiesto test the effectof apparatus competence, andgovernment's internal control system on the accountability of village financialmanagement in Rote Ndao Regency. The population of this study was all village officials in Rote Ndao Regency. Purposive sampling technique was used to select the samples.The samples of this studywere 54 village officialsthere are village heads or village treasurers in Rote Ndao Regency. The data analysis technique used the PLS (Partial Least Square) with SmartPLS 3.0 software. The results showed thatthe competence of the apparatusandgovernment's internal control systemhas a positive effect on the accountability of village financialmanagement. The results of the study contributed to the policy of the Rote Ndao government as a material consideration in revising the regulation of Minister of Home Affairs number 65 year 2017 Article 21 concerning the election of prospective village heads with an education level of junior high school or equivalent.